Forge - Anderson, Laurie Halse (New York : Atheneum Books for Young Readers, 2010)
Curzon, having matured from boy to man over the course of the winter with the army at Valley Forge, worries that someone will learn he is a runaway slave passing for free, and tries to figure out the meaning of his friendship with Isabel.
"Seeds of America."
Sequel to: Chains.
Includes bibliographical references.
Booklist
Kirkus Starred
Pub Weekly
Keywords: African Americans -- Juvenile fiction; Freedmen -- Juvenile fiction; Slavery -- Juvenile fiction; Soldiers -- Juvenile fiction; African Americans -- Fiction; Freedmen -- Fiction; Historical fiction; Slavery -- Fiction; Soldiers -- Fiction; African Americans -- Fiction; Freedmen -- Fiction; Historical fiction; Slavery -- Fiction; Soldiers -- Fiction; Pennsylvania -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; Valley Forge (Pa.) -- History -- 18th century -- Juvenile fiction; Pennsylvania -- History -- Revolution, 1775-1783 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; Valley Forge (Pa.) -- History -- 18th century -- Fiction; Pennsylvania -- History -- Fiction; United States -- History -- 1775-1783, Revolution -- Fiction; Valley Forge (Pa.) -- History -- Fiction; Historical fiction